Whispers at Dusk: Blackbird Trilogy #1 - Graham, Heather ([Place of publication not identified] : Mira Books, 2023)
Four bodies have been discovered along Europe's riverbanks, placed with care--and completely drained of blood. Pinpricks on their throats indicate a slender murder weapon, but DNA found in the wounds suggests something far more sinister. Tasked with investigating, the FBI recruits Agents Della Hamilton and Mason Carter to Blackbird, an international offshoot of the Krewe of Hunters. If you want to catch a vampire killer, you need agents who can speak with the dead.
New Book 2023 Summer.
Keywords: Vampires; Romance fiction; Paranormal fiction; Vampire fiction; Immortalism; Serial murder investigation; FICTION / Thrillers; Norway; Lillehammer (Norway)